2014
DOI: 10.1371/journal.pone.0088158
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neuron Development in Mouse Coccygeal Vertebrae and Its Relationship to Tail Biopsies for Genotyping

Abstract: A common method of genotyping mice is via tissue obtained from tail biopsies. However, there is no available information on the temporal development of sensory neurons in the tail and how their presence or absence might affect the age for performing tail biopsies. The goals of this study were to determine if afferent sensory neurons, and in particular nociceptive neurons, are present in the coccygeal vertebrae at or near the time of birth and if not, when they first can be visualized on or in those vertebrae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In a recent study, it has been suggested that in a neonatal mouse or rat, particularly prior to approximately 12 d of age, a nociceptive stimulus may not result in the conscious perception of pain due to the lack of a competent pain pathway at this age [18]. At 14-17 d after birth, mice have less ossified tails and samples can be smaller than those from adult mice [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it has been suggested that in a neonatal mouse or rat, particularly prior to approximately 12 d of age, a nociceptive stimulus may not result in the conscious perception of pain due to the lack of a competent pain pathway at this age [18]. At 14-17 d after birth, mice have less ossified tails and samples can be smaller than those from adult mice [6].…”
Section: Discussionmentioning
confidence: 99%
“…Finally these procedures, alone or in combination, can alter the overall well-being of mice, 32,33 and are also widely considered to be painful. [34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…Table shows the age(s) at which each tissue sampling method can be used. Sampling should, where possible, be done on young animals for the reasons listed below: DNA from tissues of young mice is more optimal for genotyping than that from older animals (Picazo & García‐Olmo, ). In a newborn mouse (particularly before 12 days of age), discomfort due to the sampling is reduced because the sampled tissue is not fully ossified and because the nociceptive stimulus may not result in the conscious perception of pain due to the lack of a competent pain pathway at this age (Hankenson, Garzel, Fischer, Nolan, & Hankenson, ; Silverman & Hendricks, ; Wever, Geessink, Brouwer, Tillema, & Ritskes‐Hoitinga, ). If genotyping is completed before weaning, extra animals or those of nondesired genotype can be sacrificed before separation of young animals into different cages. …”
Section: Commentarymentioning
confidence: 99%
“…Current Protocols in Mouse Biology not fully ossified and because the nociceptive stimulus may not result in the conscious perception of pain due to the lack of a competent pain pathway at this age (Hankenson, Garzel, Fischer, Nolan, & Hankenson, 2008;Silverman & Hendricks, 2014;Wever, Geessink, Brouwer, Tillema, & Ritskes-Hoitinga, 2017).…”
Section: Of 28mentioning
confidence: 99%